A generalization and improvement of Chidume theorems for total asymptotically nonexpansive mappings in Banach spaces - Chang, Shih-sen; Kim, Jong Kyu; Lee, H W Joseph; Chan, Chi Kin (Journal of inequalities and applications, 2012)
The purpose of this article is to establish some new approximation theorems of common fixed points for a countable family of total asymptotically quasi-nonexpansive mappings in Banach spaces which generalize and improve the corresponding theorems of Chidume et al. and others. 2000 AMS Subject Classification : 47J05; 47H09; 49J25.